Family-based association study of ZNF533, DOCK4 and IMMP2L gene polymorphisms linked to autism in a northeastern Chinese Han population - Liang, Shuang; Wang, Xue-lai; Zou, Ming-yang; Wang, Han; Zhou, Xue; Sun, Cai-hong; Xia, Wei; Wu, Li-jie; Fujisawa, Takashi X.; Tomoda, Akemi (Journal of Zhejiang University. B. Science, 2014)
Objective： A study in a Caucasian population has identified two single-nucleotide polymorphisms （SNPs） in ZNF533, one in DOCK4, and two in IMMP2L, which were all significantly associated with autism. They are located in AUTS1 and AUTS5, which have been identified as autism susceptibility loci in several genome-wide screens. The present study aimed to investigate whether ZNF533, DOCK4, and IMMP2L genes are also associated with autism in a northeastern Chinese Han population. Methods： We performed a similar association study using families with three individuals （one autistic child and two unaffected parents）. A family-based transmission disequilibrium test （TDT） was used to analyze the results. Results： There were significant associations between autism and the two SNPs of ZNF533 gene （rs11885327： X^2=4.5200, P=0.0335; rs1964081 ：）（2=4.2610, P=0.0390） and the SNP of DOCK4 gene （rs2217262 X^2=5.3430, P=0.0208）. Conclusions： Our data suggest that ZNF533 and DOCK4 genes are linked to a predisposition to autism in the northeastern Chinese Han population.